2007
DOI: 10.1007/s11661-006-9036-y
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Plastic Deformation of WC-Co Composites Loaded with a Spherical Indenter

Abstract: The quasi-plastic deformation behavior of cemented tungsten carbide (WC-Co) materials was studied using Hertzian indentation techniques. The indentation stress-strain curves of three WC-10 wt pct Co alloys with different hardness values demonstrate that WC-Co alloys exhibit ''quasi-plasticity'' behavior under indentation load and the increase of indentation stress vs indentation strain bears similarity to ''strain hardening'' in ductile metals. The analysis of the subsurface indentation damage shows that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…In general, ceramics are brittle materials that are unable to accommodate significant macroscopic plastic strains. However, examination of indent sites and/or indentation stress-strain behavior in several ceramic materials has shown that they may experience inelastic deformation mechanisms, such as microcracking, microcleavage, slip, and twinning, at room temperature (7,(11)(12)(13)(14)(15)(16)(17). This has led some researchers to propose the use of indentation techniques as a means of "quantifying" quasi-plastic deformation in these materials.…”
Section: Quantifying Quasi-plasticity In Ceramicsmentioning
confidence: 99%
“…In general, ceramics are brittle materials that are unable to accommodate significant macroscopic plastic strains. However, examination of indent sites and/or indentation stress-strain behavior in several ceramic materials has shown that they may experience inelastic deformation mechanisms, such as microcracking, microcleavage, slip, and twinning, at room temperature (7,(11)(12)(13)(14)(15)(16)(17). This has led some researchers to propose the use of indentation techniques as a means of "quantifying" quasi-plastic deformation in these materials.…”
Section: Quantifying Quasi-plasticity In Ceramicsmentioning
confidence: 99%
“…In order to minimize and eliminate the (1979), Bolton and Keely (1982), Sigl, Exner, and Fischmeister (1986), p. 631, Sigl and Exner (1987), Ravichandran (1994), Luyckx, Sacks, and Love (2007), and Zhang, Fang, and Belnap (2007). A. Shatov also further addresses an examination of fracture toughness within this volume in Chapter 1.10.…”
Section: Engineering Properties and Dependence On Microstructurementioning
confidence: 99%
“…Damage evolution has been investigated using a Hertzian indentation technique, which uses a near frictionless spherical indenter loaded normal to a polished surface (Zhang, Fang, et al, 2007). In addition to obtaining stress-strain curves in this work, Zhang measured and evaluated surface and subsurface microscopic and macroscopic cracking.…”
Section: Engineering Properties and Dependence On Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…refs. [9][10][11][12][13]). In this study, such protocols are adapted to investigate and document the contact mechanical response of polycrystalline diamond -PCD.…”
Section: Introductionmentioning
confidence: 99%